Proceedings of the 46th ACM Technical Symposium on Computer Science Education 2015
DOI: 10.1145/2676723.2677297
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Student Work Patterns Using Programming Exercise Data

Abstract: Web-based programming exercises are a useful way for students to practice and master essential concepts and techniques presented in introductory programming courses. Although these systems are used fairly widely, we have a limited understanding of how students use these systems, and what can be learned from the data collected by these systems.In this paper, we perform a preliminary exploratory analysis of data collected by the CloudCoder programming exercise system from five introductory courses taught in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…Overall, in line with previous studies, we observed that students' performance decreases during the course. This is in line with both the general knowledge in introductory programming as well as the literature where students' performance in online programming environment has been analyzed [18]. However, when contrasting our results to those in [18], students in our context are working in a traditional programming environment, and the majority of the course assignments expect that the students implement more than a single function -thus, generalizing the previous results to a new context.…”
Section: Discussion 51 Overall Performance In the Coursesupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, in line with previous studies, we observed that students' performance decreases during the course. This is in line with both the general knowledge in introductory programming as well as the literature where students' performance in online programming environment has been analyzed [18]. However, when contrasting our results to those in [18], students in our context are working in a traditional programming environment, and the majority of the course assignments expect that the students implement more than a single function -thus, generalizing the previous results to a new context.…”
Section: Discussion 51 Overall Performance In the Coursesupporting
confidence: 89%
“…With research question one, we aim to both validate previous results by Spacco et al [18] in a new context, and to extend the work by analyzing students' performance changes from week to week. These changes are discussed in the light of the content taught in the course.…”
Section: Research Design 31 Research Questionsmentioning
confidence: 85%
See 1 more Smart Citation
“…Often, these studies are based upon snapshots of the students' code and recordings of their activities, investigating how these habits correlate with the students' performance. Several researchers have noted that lower performing students usually take longer to complete the exercises [1], [55], [52]. Prior research that has tracked student activities during their coding sessions has also shown that better performing students usually analyze the code in a more logical manner and spot the issues faster, while lower performing students have difficulty localizing problems [55], [43].…”
Section: Social Learning and Study Habitsmentioning
confidence: 99%
“…Spacco [2] collected student programming data across five semesters and three institutions. Spacco found that as students do incrementally-harder exercises, students' scores tended to decrease, whereas the chance of submitting correctly compiling code tended to increase.…”
Section: Researchers [1][2][5][9]mentioning
confidence: 99%